Gender differences in psychological help-seeking attitudes: a case in Türkiye - Güney, Esra; Aydemir, Ahmet Fatih; Iyit, Neslihan; Alkan, Ömer (Frontiers in Psychology, 2024)
Background/aim: Mental disorders pose a substantial public health challenge within the overall disease burden. This study aims to determine the factors associated with seeking psychological help among individuals experiencing depression according to gender differences in Türkiye. Methods: The study utilized microdata from Türkiye Health Survey conducted by the Turkish Statistical Institute in 2016, 2019, and 2022. Binary logistic regression analysis was employed to determine the factors associated with seeking psychological help. Results: The study’s findings reveal that variables such as survey year, age, education level, employment status, general health status, disease status, depression status, day service status in the hospital, daily activity status, tobacco use status, and alcohol use status are associated with the status of receiving psychological help. Conclusion: Gender-specific analysis indicated variations in the significance and impact of these variables among individuals seeking psychological help. In the development of preventive strategies for mental health protection, special attention should be given to factors associated with the psychological help-seeking behaviour of both women and men. Prioritizing and addressing these factors will contribute to more effective mental health interventions.